Some integrative management strategies to decrease doses of herbicides in agriculture - Abriz, salar Farhangi (Journal of Aridland Agriculture, 2017)
Over dose using of herbicides is one of the major problems in crops and horticulture productions. Human food safety and economical production of agricultural products are the main target of new agronomy and plant scientists. Integrative management is one of the new programs for reducing herbicide doses in agriculture. This program includes many physiological and physicochemical methods for controlling herbicide uses in farms and orchards. This article explain some of these methods such as using surfactants, water quality in spraying, using magnetic fields, controlling the nitrogen content of soil, using a suitable formulation and powerful cultivars and genotypes in agriculture and the effects of this reduction in herbicide doses on plants behavior and weeds controlling. According to this method integrative management can be beneficial in crop production and farmers must be using of this management method in their farms.Â 